Adwa' al-Bayan Karya al-Shanqiti Sebagai Kitab Tafsir al-Qur’an bi al-Qur’an - Izza Rohman (JOURNAL OF QUR'AN AND HADITH STUDIES, 2013)
This article examines the intensiveness, centrality and nature of inner-Quranic exegetical method – a method sometimes considered as providing more objectivity – employed by the Mauritanian-born exegete Muhammad al-Amin al-Shanqiti (19071973) in his Adwa’ al-Bayan. It compares the statistics of cross-referring of verses in this tafsir to that in other tafsirs known as also applying the method – in an attempt to show the level of its intensiveness. In addition, it also seeks to assess the centrality of this method in Adwa’al-Bayan by comparing statistical references to sources outside the Qur’an. In reviewing Adwa’al-Bayan’s style of interpreting al-Qur’an with al-Qur’an, this article looks at its application in the commentary of Sura Yasin.